ANALISIS QUALITY OF SERVICE (QOS) TRAFIK MULTIMEDIA PADA WIRELESS LOCAL AREA NETWORK DI LABORATORIUM TEKNIK ELEKTRO UPN VETERAN JAKARTA MENGGUNAKAN WIRESHARK DAN PRTG - Inez Innocentia Rahawarin (2023)
Monitoring and measuring Quality of Service (QoS) and Quality of Experience (QoE) is a method to assess and improve the quality of telecommunication services, especially in areas with many users such as the Electrical Engineering Laboratory of UPN Veteran Jakarta. Based on the survey results, many problems experienced by Wi-Fi users are related to the availability, accessibility, retainability, and stability of the multimedia application services accessed. In this research, the analysis of QoS parameters was carried out for three multimedia applications: WhatsApp Desktop Call, Zoom Meeting, and the UPNVJ LeADS web. Data collection was carried out using Wireshark and PRTG, as well as the router admin panel web and Command Prompt. Based on monitoring results, the network can experience a decrease in quality when connected to more than 5 devices simultaneously, downtime conditions occur quite frequently, reaching 54% in a day, and the average amount of traffic that passes on one device is 4,34 Mbps. Based on measurements and average calculations of the QoS parameters, the highest throughput value reaches 102,09 Kbps on UPNVJ LeADS web, the worst delay value reaches 521,39 ms on WA call, the jitter value reaches 1,21 ms on WA Call, and the packet loss value reaches 2,16% on Zoom Meeting. The most common problem experienced is the no internet condition on the Wi-Fi network. The solution for optimizing this network can be done by administration setting and network management.